Respuesta :

Answer:

Step-by-step explanation:

12x² + 17x -5 = 12x² + 20x - 3x - 5

                    = 4x(3x + 5) -(3x + 5)

                    = (3x + 5)(4x - 1)

6x² + 7x - 5 = 6x² + 10x - 3x - 5

                   = 2x(3x + 5) -(3x+5)

                   = (3x + 5)(2x - 1)

[tex]Area =\dfrac{1}{2}*b*h[/tex]

         [tex]= \dfrac{1}{2}*(4x -1) *\dfrac{6x^{2}+7x-5}{12x^{2}+17x-5}\\\\=\dfrac{1}{2}*(4x-1)*\dfrac{(3x+5)(2x-1)}{(3x+5)(4x-1)}\\\\=\dfrac{1}{2}*1*\dfrac{ 2x-1}{1}\\\\=\dfrac{2x-1}{2}[/tex]

Hope you could understand.

If you have any query, feel free to ask.

Ver imagen Аноним